PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIIIA SMP NEGERI 1 ROKAN IV KOTO - Meydia Rahmi; Rini Dian Anggraini; Susda Heleni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research is a Classroom Action Research (CAR) which aims to improve the learning process and the result of learning mathematics by applying Discovery Learning model. Subjects in this research were students of class VIIIA SMP Negeri 1 Rokan IV Koto in the second semester 2018/2019 academic year consisting of 12 male students and 14 female students. The research instruments used are mathematical learning instruments (syllabus, Lesson Plans and Student Worksheet) and data collection instruments (observation sheets and learning outcomes test sheets). The observation sheet is used to obtain data on teacher and student activities during the learning process, while the mathematics learning outcomes test is used to obtain learning outcomes data. Based on the analysis of the observation sheet, it was found that the implementation of the learning process from cycle I to cycle II had improved. The results of learning mathematics of KBM students' knowledge indicators increased from a base score of 50% (13 students) to 57,69% (15 students) in the first cycle and increased to 69,23% (18 students) in the second cycle. The results of the KBM students' mathematics learning skills indicators experienced an increase from the base score of 57,69% (15 students), increasing to 69,23% (18 students) in the first cycle and increasing to 76,92% (20 students) in the second cycle. With these results it can be concluded that in learning there is an improvement in the learning process and improvement in the mathematics learning outcomes of class VIIIA SMP Negeri 1 Rokan IV Koto in the second semester 2018/2019 academic year through the application of the Discovery Learning model in the subject matter of Pola Bilangan.Keywords : Students’ Math Achievement, Discovery Learning Model, Clasroom Action Research.